City blindness: Visuality and modernity in the works of Iza Caparas, Farley del Rosario and Daniel Aligaen - Devilles, Gary C (Archīum Ateneo, 2012)
For Georg Simmel, humans confront their basic contradiction in the city, and such contradiction warrants critical assessment to help in the long tradition of articulating the problematic development of cities or metropolises, and hopefully advocate for the kind of life we want. This contradiction is a corollary to the modern visual aesthetics of young, contemporary artists such as Iza Caparas, Farley del Rosario and Daniel Aligaen. Their works not only depict the city or urban living; also their styles or sense of aesthetics are informed on a larger scale by the geopolitics of the ’70s up to the present, the influence of the early modernist artists, and their own estimation as well of what is happening in the country. This paper uses visual impairment or blindness as a trope for modernist aesthetics. The contradiction of city life produces this particular problematic vision that is then appropriated by these young painters. In this paper I am guided by three important questions: How do I understand the city and its contradictions? How is the city depicted in the paintings of young contemporary artists? How do I talk about modernist paintings and aesthetics in terms of the dynamics of city or urban life?